Experimental Investigation and Numerical Modeling of the Bond Shear Strength of Multi-layered 6000 Series Aluminum Alloys - Herrmann, Jürgen; Suttner, Sebastian; Merklein, Marion (Procedia Engineering, 2017)
The use of high-strength aluminum alloys is one key factor for the realization of lightweight design in industrial applications. Besides alloying, it is possible to produce high-strength sheet materials using the Accumulative Roll Bonding (ARB) process. Based on a repetitive stacking and roll bonding process, multi-layered sheets with a nanocrystalline grain structure are produced. The bond formation is created by a cold welding process due to the high pressure in the rolling gap and cracks in the oxide film of the aluminum sheet material caused by the thickness reduction. The experimental investigation of the bond strength is crucial for the assessment of the formability of the multi-layered sheet material. High bonding quality is necessary in order to prevent failure mechanisms like delamination in subsequent forming operations. Furthermore, a numerical model, which contains discrete layers over the sheet thickness as well as their bonding mechanisms will be implemented in finite element analysis. This enables a process layout for forming operations by the prediction of delamination effects. Within this investigation, an experimental test method is presented to characterize the bond shear strength of multi-layered sheet material. The use of an optical strain measurement system enables the identification of the material behavior over the sheet thickness during the shear test. For this investigation a 16-layered aluminum alloy AA6014 is used. However, the bond shear strength of the last bonded respectively middle layer of the sheet material is investigated. The 16-layered material has 15 bonds over the thickness but the one in the middle has the lowest bond strength as it was only roll bonded once compared to the others, which were rolled at least twice. The bonding mechanisms are modelled using a tiebreak contact formulation in the finite element software LS-DYNA. Concluding, the numerical model is validated by comparison with the experimental results.
EAM Import::2019-03-14